2017
DOI: 10.1016/j.jfda.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidant activity and major chemical component analyses of twenty-six commercially available essential oils

Abstract: This study analyzed 26 commercially available essential oils and their major chemical components to determine their antioxidant activity levels by measuring their total phenolic content (TPC), reducing power (RP), β-carotene bleaching (BCB) activity, trolox equivalent antioxidant capacity (TEAC), and 1,1-diphenyl-2-picrylhydrazyl free radical scavenging (DFRS) ability. The clove bud and thyme borneol essential oils had the highest RP, BCB activity levels, and TPC values among the 26 commercial essential oils. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 42 publications
(42 reference statements)
5
21
3
Order By: Relevance
“…Further comparison of our results with literature data was not possible due to the different origin of vegetal matrix, AOC assays procedures and expression of results. However, the values obtained were comparable with those usually reported for essential oils (Ruiz-Navajas et al, 2013;Wang et al, 2017;Yashin et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Further comparison of our results with literature data was not possible due to the different origin of vegetal matrix, AOC assays procedures and expression of results. However, the values obtained were comparable with those usually reported for essential oils (Ruiz-Navajas et al, 2013;Wang et al, 2017;Yashin et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…The results of total phenols in our study were found to be higher than the values reported in literature for [58]. The observed antioxidant potential should be addressed to the phenolic oil constituents such as thymol and carvacrol [59].…”
Section: Tpc and Tfccontrasting
confidence: 86%
“…4) Not detected or larger retention indices than 3000 in Supelcowax 10 column. 5) Not detected or less than 1.0 µg/100 g. 6) Tentatively identified based on mass spectral data only due to lack of authentic standard compound. 7) Compounds used for antioxidant activity assays.…”
Section: Chemical Composition Of the Steam-distilled Essential Oil (Smentioning
confidence: 99%
“…More recently, essential oils and some of their isolated components are increasingly being used in various commercial products such as foods, cosmetics, perfumes, household cleaning products and hygiene products, and medicinal applications [2]. These compounds have been reported to have various biological activities including antimicrobial, antioxidant, antiviral, antiplatelet, antithrombotic, antiallergic, anti-inflammatory, antimutagenic, and anticarcinogenic properties [4][5][6].…”
Section: Introductionmentioning
confidence: 99%